Remidiasi Menggunakan Model Kooperatif STAD Pada Materi Momentum Dan Impuls Kelas X SMA Al Islam 1 Surakarta - Tri Muzaeni; Ahmad Fauzi; Dwi Teguh Rahardjo (Universitas Sebelas Maret, 2023)
The purpose of this study was to: find out that Remediation of Physics learning using the STAD (Student Teams Achievments Divisions) cooperative learning model can improve the cognitive abilities of students of class X MIA 3 on Momentum and Impulse material.This research is a quasi-experimental study using one class. This study uses a one-group pretest-posttest model. The data analysis technique uses quantitative techniques. Quantitative analysis is used to test the proposed hypothesis. The submission of the hypothesis in this study uses the t-test statistic (1 tail) to show an increase in students' cognitive physics abilities after the action.Based on the results of data analysis and discussion obtained from the research, it can be concluded that: Remediation of Physics Learning Using the STAD Cooperative Learning Model can improve the cognitive of class X MIA 3 SMA Al Islam 1 Surakarta on Momentum and Impulse material. Based on the hypothesis test that t count is greater than t table, namely tcount = 9.495> ttable = 1.68830 which indicates that there is an increase in students' physical cognitive abilities. The amount of increase based on the gain index is 0.58 which is included in the medium category.